COST-EFFECTIVENESS EVALUATION OF VANCOMYCIN THERAPEUTIC DRUG MONITORING WITH TARGET AUC/MIC AT CU CHI REGIONAL GENERAL HOSPITAL DURING 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the cost-effectiveness of vancomycin therapeutic drug monitoring based on the area under the concentration–time curve to minimum inhibitory concentration ratio - AUC/MIC (TDM AUC).Subjects and Methods: The study was conducted based on data from insured patients receiving vancomycin at Cu Chi Regional General Hospital during two periods: before TDM implementation (01-06/2024) and after TDM application (01-06/2025). The analysis was performed from the healthcare system perspective and focused on direct medical costs and clinical outcomes.Results: The implementation of TDM AUC was identified as a dominant strategy, simultaneously improving clinical outcomes and reducing costs, saving 9.4 million VND per additional clinical response achieved. Furthermore, TDM AUC significantly reduced the risk of acute kidney injury (AKI), corresponding to savings of approximately 8.7 million VND per AKI case prevented. One-way sensitivity and probabilistic analyses demonstrated consistent results, maintaining cost-effectiveness advantages across most iterations.Conclusion: This study provided additional economic evidence for TDM AUC implementation. These results provide a foundation for treatment decision-making and broader application in healthcare facilities with similar conditions.
Keywords: Cost-effectiveness, Vancomycin TDM, Cu Chi Regional General Hospital